Importance of Epigallocatechin and its Health Benefits - Shahrajabian, Mohamad Hesam; Sun, Wenli; Cheng, Qi (Free Radicals and Antioxidants)
Natural products have a wide range of diversity of multidimensional chemical structures which play a vital role which show the important nature as golden source for achieving the herbal drug discovery. Literature survey was accomplished using multiple databases including PubMed, Science Direct, ISI web of knowledge and Google Scholar. Epigallocatechin-3-gallate is the most abundant tea polyphenol, followed by other polyphenols, namely, catechin, epicatechin, epicatechin-3-gallate and epigallocatechin.The most important pharmacological activities of EGCG are antineoplastic, HIV infection, hypertension and associated complications, type II diabetes mellitus, its usage as cardioprotective, hepatoprotective, nephroprotective and its application in Alzheimer, Parkinson and Osteoporosis. Natural products have played a key role in drug discovery and development in modern days.
Keywords: Natural Compounds; Medicinal Plants; Phloretin; Epigallocatechin